Earthen Stūpas of Pre-ancient Nepāl - Ranjitkar, Junu Basukala (Historical Journal, 2020)
The initial stūpas of pre-ancient Nepal were erected using earthen mounds. However, thePāli and Sanskrit Buddhist texts do not mention that stūpas have to be earthen mounds.Only the Pāli Jātaka story Sujāta mentions the presence of earthen mound stupa containingthe relics of a deceased person. The earthen mound stūpas were initially made in the Indiansub-continent after Buddha’s Mahāparinibbāna. There were ten preliminary stūpas thatwere erected containing the Buddha’s relics, a vessel and ashes. One of them, Rāmagrāmastūpa, is still in existence in its original form. When Emperor Asoka converted to Buddhism,he erected 84,000 stūpas with small relics of the Buddha, extracting those relics from theseven original stūpas. Not only that, he also went on to enlarge the size of a few originalstūpas using bricks in the construction process. Piprahavā stūpa of Kapilvastu, Nibbānastūpas of Kanakamuni and Krakuchhanda, twin stūpas of Dhamnihavā were renovated byenclosing the earthen mound with bricks. The Bhishvā stūpa of Birgunj and three stūpasof Pātan and a stūpa of kothuvahī are still in existence in their original form. However, allthese stūpas are enclosed by walls built in the later part of the centuries to preserve them.The Chārumatī stūpa and the Yampi stūpa were built in Vajrayāna tradition. However, inrecent times the infrastructure developments in the cities have led to the use of modernmaterials like cement and white plaster and altering even the architectural styles of someof the stupas. The north-east section of Chārumatī stūpa and the Yampi stūpa have sufferedthis impact.